Rearrangement Strategy for the Preparation of Polymers With π-Conjugated Structures - Tang, Jian; Xie, Tinghao; Geng, Jieting; Hua, Jing; Wang, Zhaobo (Frontiers in Chemistry, 2021)
π-Conjugated polymers are usually prepared by polymerization only. In this perspective article, typical synthesis methods of conjugated polymers are briefly summarized, and a novel strategy for preparing conjugated polymers by rearrangement is proposed. During the metalation process, many conjugated structures were generated in polybutadiene by double bond migration. The effects of reaction time, temperature, and catalyst dosage on the product structure were investigated. Moreover, the structure of the products was confirmed by FTIR, 1H NMR, and 2D HSQC NMR spectra. Thus, a possible reaction mechanism was proposed, in which polybutadiene generates allylic carbanions in the presence of n-butyllithium, and then the double bonds migrate through the carbanions rearrangement to generate many conjugated structures in the backbone chain. The method shows promise in facile and low-cost synthesis of conjugated polymers without the need for precious metal catalysts.